Market Structure and Competition Price in Islamic Economics - Dadang Mulyana (UIN Sunan Gunung Djati Bandung, 2018)
This article will discuss market structure and competition prices in islamic economics. Literature searching is the method used in writing this article. This article found that market in Islam is defined as a means of meeting between seller and buyer, where the buyer came to the market with a demand for goods membewa certain to meet with the seller that brings offers the same goods as well. And the outcome of the meeting will produce an agreement between the seller and the buyer of the price level and the number of items in the transaction. If an agreement between the seller and the buyer then there was a provision of an item in the transaction. The market structure has a notion that some form of management of the producer to the market based on their characteristics, for example, such as the type of product produced, the number of companies in an industry. Easy or not exit or enter the industry and the role of advertising in industry activity. Perfect competition is a market structure that is most ideal for systems market is considered to ensure their activities to produce goods or services is high. The conclusion of the article are: however, in practice it is not easy to realize a market that has a structure of perfect competition. pricing is one of the practices that are not allowed by the Islamic Shari'a. Government or who have economic power do not have the right and authority to determine the fixed price of a commodity, unless the government has provided for the trader’s sufficient quantities to be sold using a price has been agreed. Tabi'at (fixed) This we can see from how the attitude of the prophet Muhammad pbuh on the issue. When visited by a companion to ask for fixing the price, the Prophet pbuh stated his rejection.